Countering al Qaeda An Appreciation of the Situation and Suggestions for Strategy - Jenkins, Brian Michael (RAND Corporation, 2002)
This monograph reviews events since the terrorist attacks of September 11, 2001, and discusses the current state of al Qaeda and the kinds of actions that can be expected of it in the future. Al Qaeda constitutes the most serious immediate threat to the security of the United States, so the campaign against terrorism must remain focused. The monograph describes the central elements that must be emphasized in the next, more-complex phase of that campaign.